Bills of quantities: raison d’etre? - Bandi, Shamsul Hadi (IIUM Press, 2011)
There was a call for more research to be focused on core areas of quantity surveying including research concerning the state of BQ in Malaysia. This paper seek to respond to the call by presenting important points from literatures concerning research undertaken under the theme of BQ, in order to support and justify the need to conduct research within the ambit of Malaysian construction industry. Objectives of this paper are: (1) To examine in detail the purpose, functions, BQ format and types identified from the literatures, and (2) To provide a snapshot summary on researches undertaken on BQ related issues. The ultimate aim of this paper is to re-introduce the basic of BQ with support of literatures and finally suggest „immediate‟ research directions towards BQ related issues in Malaysia. The paper has employed an extensive literatures review and concludes that research into BQ in Malaysia is feasible and of utmost needed.